Structure Determination of a Natural Juvenile Hormone Isolated from a Heteropteran Insect. (19th February 2012) - Kotaki, Toyomi; Shinada, Tetsuro; Numata, Hideharu
Abstract : Juvenile hormone (JH), which occurs in several forms in different insects, is one of the most important insect hormones. The structure of JH in Heteroptera has not been elucidated until recently, although insects in this suborder have long been used as experimental animals for JH research. Here we review the structure determination of a novel JH in a stink bug, Plautia stali, which was named juvenile hormone III skipped bisepoxide [JHSB3 : methyl (2 R, 3 S, 10 R )-2, 3;10, 11-bisepoxyfarnesoate], based on the arrangement of two epoxides at C2, 3 and C10, 11 with a skipped double bond at C6, 7.